Portuguese representations in the Semana Santa ritual in Larantuka - Yohana, Saferi (Yayasan Irwan Abdullah Cendekia, 2023)
The encounter of Indonesian society with foreign cultures leaves a mark on a culture, leaving traces in the form of narratives and symbols. In Larantuka, the encounter of local culture with the Portuguese leaves the Semana Santa tradition or Easter tradition which in the oral narrative and ritual process still presents the Portuguese style. This research was conducted to find out how the presence of Portuguese culture functions in the Semana Santa tradition in Larantuka; and why Portuguese heritage is maintained and preserved in the tradition. Data collection utilized participatory observation, interview, and literature study methods. The results showed that the Semana Santa ritual as a Portuguese heritage still takes place as an annual ritual, the use of Portuguese language in the ritual, symbols, and the Confraria brotherhood formed by the Portuguese. Three important points that become the reason for the Portuguese presence in the Semana Santa ritual are the acculturation process, narratives in collective memory, and the obedience of tradition actors in carrying out ancestral messages.